Strategi Digital Marketing untuk Meningkatkan Omset Penjualan Pelaku Usaha Mikro Kecil dan Menengah (UMKM) di Masa Pandemi - Fitria Andestri (Peradaban: Jurnal Pengabdian Masyarakat, 2025)
The Covid-19 pandemic has significantly impacted various sectors, particularly Micro, Small, and Medium Enterprises (MSMEs), which have experienced a sharp decline in sales revenue. The economic disruptions caused by the pandemic have posed challenges for MSME actors, necessitating adaptive strategies to sustain their businesses. This study aims to analyze the impact of Covid-19 on MSMEs and explore digital marketing strategies as a potential solution to mitigate revenue losses. The research employs a qualitative approach using secondary data collected from scientific journal articles, official documents, and other relevant sources. The findings indicate that the pandemic has led to reduced consumer purchasing power, supply chain disruptions, and business operational limitations, thereby affecting MSME profitability. However, digital marketing emerges as an effective strategy for business resilience by enabling broader market reach, cost efficiency, and enhanced customer engagement. The study highlights key digital marketing strategies, including social media marketing, search engine optimization (SEO), and e commerce adoption, which have proven beneficial in helping MSMEs adapt to the changing market dynamics. The results suggest that digital transformation is crucial for MSME sustainability, especially during crisis periods. This study contributes to the literature on MSME survival strategies and provides practical insights for policymakers and business practitioners in fostering digital adoption. Further research is recommended to explore the long-term impact of digital marketing on MSME performance post-pandemic.